Medicine information needs of patients: the relationships between information needs, diagnosis and disease. Issue 2 (2nd April 2008) - Duggan, C; Bates, I
Abstract : Objective: To identify medicine information needs of patients and explore differences in information needs between different disease groups of patients. Design: Semistructured interviews with general medical patients selected via convenience sampling. Setting: Patients were recruited while inpatients during a hospital stay or as outpatients attending a specific clinic at the hospital. Main outcome measures: Patients' responses to standardised data-collection tools, including previously validated scale, the Extent of Information Desired scale (EID) to identify their information needs. Results: Data from interviews with 1717 patients were included in the analysis. Each item on the EID scale was scored on a Likert scale (from 1 to 5). The internal consistency of the scale in this sample was good (coefficient α = 0.78). Scores to the EID scale correlated with age and socio-demographic variables. The extent of information desired positively correlated with socio-economic status (Pearson's r = 0.29, p<0.001). The extent of information desired negatively correlated with the patient's age (Pearson's r = −0.32, p<0.001), implying that medicine-information desires decreases with age. Subsequently, significant differences were found in the extent of information desired between disease categories, which remained significant when controlling for age (ANCOVA, F6, 1703  = 26.04, p<0.001, partial η2 0.084 (ie, 8.4% "effect size"). Disease categories included: cardiovascular, gastrointestinal, respiratory, endocrine, diabetic, oncology. Patients with endocrine and diabetes diagnoses expressed high desires for information, whereas patients with cardiovascular and respiratory diagnoses expressed low desires for information. From these findings, both the disease and the age of patient are principal influences on desires for medicine information. Conclusions: These findings suggest that the diagnosis and disease have a significant bearing on patients' medicine-information desires and recommend that healthcare professionals view patients as individuals when providing information that meets their needs. It will be important for healthcare professionals to identify and understand that patients with different diseases have different desires for information about their disease and their drugs which may influence the way they take their medicines and subsequently the ways we manage their long-term disease. We need to determine if the EID scale is an efficient and effective way to identify patients' desires for drug information and a useful tool for practitioners to effectively target interventions in healthcare provision over time.